Gender Relationships In Natasha Josefowitz Poems Impressions From An Office (2014) Gut Is Data (2018) He Can/She Can’t (2019) - Ferliani , Dini Ferliani M.K; Moelier, Dahlia D.; Asyrafunnisa, Asyrafunnisa (Fakultas Sastra, Universitas Bosowa, 2025)
The objective of this research were to find out the forms of patriarchy and how the equality of feminism reflects the gender relationship in Natasha Josefowitz poems Impressions from An Office (2014), Gut Is Data (2018), He Can/ She Can’t (2019). Method that used in this research was qualitative descriptive method. The result showed that there were 2 forms of patriarchy that affect gender relationship in the poems based on Walby’s theory they were gender discrimination which is the most dominant form and violence against women. But, in the poem Gut Is Data the researcher did not found the form of patriarchy types violence against women. There were 2 types of equality of feminism that reflected the gender relationship based on Jaggar theory in Natasha Josefowitz poems namely Women had the same natural rights as men and Woman are interpreted as rational creatures who had control like men. Jaggar mentioned there were 5 types of equality of feminism but in Natasha Josefowitz selected poems the researcher only found 2 types of them. In the poem Impressions from An Office the researcher did not found equality of feminism.